In search of a reciprocal relationship in dessert cafés: linking customer perceived innovativeness to value co-creation behavior - Ling, Esther Sii Wei; Chua, Bee-Lia; Han, Heesup (Nature, 2023)
This study examined a conceptual model encompassing perceived innovativeness, perceived values, attitude, and customer value co-creation behavior in the context of dessert cafés. An online survey was conducted with customers of dessert café chains based in Malaysia. The results indicated that menu innovativeness had the highest contribution to perceived innovativeness, followed by experiential innovativeness. The study found that perceived innovativeness improved the value of money, evoked positive emotions, and enhanced social image. In highly innovative dessert cafés, positive emotions led to a positive attitude and, in turn, increased willingness to co-create value. This study provides valuable insights for dessert café businesses by emphasizing the need to foster innovation and create emotionally satisfying experiences to enhance customer engagement in co-creation activities.